2017
DOI: 10.1089/thy.2016.0409
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of Euthyroidism and Clues for Early Diagnosis of Thyroid Dysfunction: Tehran Thyroid Study

Abstract: This study shows that after a six-year follow-up in an iodine sufficient area, 6.7% of euthyroid subjects were found to progress to thyroid dysfunction, in particular subclinical hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 24 publications
4
38
1
Order By: Relevance
“…Moreover, owing to the lack of subpopulation-specific TSH reference in our area, we were unable to use subpopulation-specific TSH reference ranges to screen thyroid disorders in the population. Finally, most published studies on the associations of obesity with hypothyroidism and TAI in adults uniformly used a generic reference range of TSH for adults with different ages, sex and BMI (Table 7 ), which followed current clinical guidelines to define hypothyroidism and SCH (Knudsen et al, 2005 ; Asvold et al, 2009 ; Gopinath et al, 2010 ; Marzullo et al, 2010 ; Pearce et al, 2013 ; Jonklaas et al, 2014 ; Amouzegar et al, 2017 ; Chaker et al, 2017 ; Valdés et al, 2017 ). Therefore, our study also used a generic reference range of TSH to diagnose hypothyroidism and SCH for adults with different ages, sex and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, owing to the lack of subpopulation-specific TSH reference in our area, we were unable to use subpopulation-specific TSH reference ranges to screen thyroid disorders in the population. Finally, most published studies on the associations of obesity with hypothyroidism and TAI in adults uniformly used a generic reference range of TSH for adults with different ages, sex and BMI (Table 7 ), which followed current clinical guidelines to define hypothyroidism and SCH (Knudsen et al, 2005 ; Asvold et al, 2009 ; Gopinath et al, 2010 ; Marzullo et al, 2010 ; Pearce et al, 2013 ; Jonklaas et al, 2014 ; Amouzegar et al, 2017 ; Chaker et al, 2017 ; Valdés et al, 2017 ). Therefore, our study also used a generic reference range of TSH to diagnose hypothyroidism and SCH for adults with different ages, sex and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroid disease has emerged as the main cause of thyroid dysfunction after the frequency of goiter caused by iodine deficiency decreased following compulsory salt iodination in developing countries (13)(14)(15)(16). Worldwide, the most common conditions associated with thyroid dysfunction are overt and subclinical hypothyroidism (10,(17)(18)(19) due to autoimmune Hashimoto's thyroiditis (20)(21)(22). Among other features, the presence of serum antithyroperoxidase antibodies (TPOAb) is the main diagnostic element of this condition (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…These autoantibodies are also frequently present in euthyroid subjects, particularly women, even within the normal range for thyrotropin (TSH). TPOAbs level is one of the predictive factors for conversion from euthyroidism to thyroid dysfunction [12]. Recently published data on 10-year observation of TPOAbs variations in a population-based prospective study in Iran showed an increasing trend in TPOAbs levels over time accompanied by the rise in hypothyroidism incidence [13].…”
Section: Characteristics Of Tpoabsmentioning
confidence: 99%